Understanding the Concept of Al-Ibtila' (Trial) in Personality Development: The Muslim Flood Victims' Experience - M. Khairul Naim; Syed M. Hilmi; S. Che Zarrina; S. Nurul Salikin; Khadijah M. Hambali; Wan Adli; Azmil Z. Abidin; M. Anuar Mamat; Joni T. Borhan; Faizuri A. Latif; Ali G. Saged; M. Hazim Azhar; et al. (Econ Journals, 2024)
Vol 6, No 7S